Strategic Mastery: Examining The Marketing Mix Implementation At One Of The Outdoor Equipment Business Brands - Sri Rahayu; Sri Astuti; Camelia Safitri (UNIVED Press, 2025)
This study aims to analyze the implementation of the marketing mix strategy at One of the outdoor equipment business brands. The method used is descriptive qualitative, with data collection through interviews, observations, and documentation. The results show that the brand successfully utilizes the 4P marketing mix elements (product, price, promotion, and place) to attract consumer interest and increase sales. The products are known for their high quality and suitability for the outdoor adventure market. The pricing strategy is set considering competition and consumer response. Promotion is effectively carried out through social media and e-commerce. Store location selection is also strategic to enhance accessibility and customer convenience. However, the brand needs to continue innovating and adapting to rapidly changing consumer trends to maintain its position in the global market.